Bioaccumulation of some Heavy Metals in Red mullet (Mullus barbatus) and Common pandora (Pagellus erythrinus) in Zliten Coast, Libya - Keri Alhadi Ighwela; Ragab Farag Al-Kazaghly; Mohamed Hamid (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight •  Investigated in heavy metal bio-accumulation in red mullet (Mullus barbatus) and Common pandora (Pagellus erythrinus) collected in Zliten Coast, Libya. • Based on the samples collected, the muscle tissue of fish species may be considered suitable for human consumption. • The metal concentration levels observed were in range of acceptable limits proposed by regulations of WHO and FAO.